Effects of Mulberry on The Central Nervous System: A Literature Review - Tam, Dao N. H.; Nam, Nguyen H.; Elhady, Mohamed Tamer; Tran, Linh; Hassan, Osama Gamal; Sadik, Mohamed; Tien, Phan Thi My; Elshafei, Ghada Amr; Huy, Nguyen Tien (Current Neuropharmacology, 2021)
Background: Mulberry, including several species belonging to genus Morus, has been widely used as a traditional medicine for a long time. Extracts and active components of mulberry have many positive neurological and biological effects and can become potential candidates in the search for new drugs for neurological disorders. Objectives: We aimed to systematically review the medical literature for evidence of mulberry effects on the central nervous system. Methods: We conducted a systematic search in nine databases. We included all in vivo studies investigating the effect of mulberry on the central nervous system with no restrictions. Results: We finally included 47 articles for quality synthesis. Our findings showed that mulberry and its components possessed an antioxidant effect, showed a reduction in the cerebral infarct volume after stroke. They also improved the cognitive function, learning process, and reduced memory impairment in many animal models. M. alba and its extracts ameliorated Parkinson's disease-like behaviors, limited the complications of diabetes mellitus on the central nervous system, possessed anti-convulsant, anti-depressive, and anxiolytic effects. Conclusion: Mulberry species proved beneficial to many neurological functions in animal models. The active ingredients of each species, especially M. alba, should be deeper studied for screening potential candidates for future treatments.
Keywords: antidepression